2014
DOI: 10.1097/md.0000000000000354
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Plasma Renin Activity

Abstract: The plasma renin activity (PRA) is affected by a number of environmental factors. However, significant heritability has been shown for the activity. A hypothesis that a candidate regulatory single-nucleotide polymorphism, C-5312T, of human renin gene should have a significant effect on PRA was elucidated and updating of independent determinants of PRA was attempted.Cross sectional study.Outpatient study.We enrolled consecutive 810 subjects who had consulted our hospitals for lifestyle-related diseases.Genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…High heritability estimates were reported for plasma renin activity in a recent investigation,[ 9 ] and we have also demonstrated in a recent report that a renin gene variant was associated with plasma renin activity as a genetic factor [ 17 ]. Each PRA value by genotype for C-5312T tended to be in fair accordance with the tissue expression levels; however, they did not reach the level of statistical significance in this study.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…High heritability estimates were reported for plasma renin activity in a recent investigation,[ 9 ] and we have also demonstrated in a recent report that a renin gene variant was associated with plasma renin activity as a genetic factor [ 17 ]. Each PRA value by genotype for C-5312T tended to be in fair accordance with the tissue expression levels; however, they did not reach the level of statistical significance in this study.…”
Section: Discussionsupporting
confidence: 77%
“…REN C-5312T is one of the rare validated genetic variants with reports that have shown their effects at the genetic transcriptional level[ 16 ] and also at the plasma activity level. [ 17 ] In this study, we evaluated the renal expression level of REN in human renal tissues in respect to REN genetic variants for the first time. Tissue expression levels of REN were significantly higher in T allele homozygotes than in heterozygotes and C allele homozygotes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies of the human renin revealed the transcriptional mechanism [ 5 7 ], the gene expression [ 12 ] and genetic and environmental factors [ 13 ]. CCB is thought to up-regulate renin gene transcription via catecholamines–β1 adrenoceptor–cAMP–PKA–CREB–CRE pathway [ 14 ] and Ca–Ref1–nCaRE pathway [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the article “Determinants of Plasma Renin Activity Role of a Human Renin Gene Variant as a Genetic Factor”, 1 which appeared in Volume 93, Issue 29 of Medicine , an rs number at the end of the Subjects and Methods section was incorrectly presented. In the sentence “Recently, the variant C-5312T is assayed using the TaqMan method (rs 12750854) with common PCR conditions recommended by the manufacturer (Applied Biosystems, Foster City, CA),” rs 12750854 should have read rs 12750834.…”
mentioning
confidence: 99%